Multidrug Resistant Vibrio Species Isolated From Abattoir and Aquaculture Environment in Ebonyi State, Nigeria - stanley Onuoha; Felicia Oko; Collins Okafor; Kenneth Ovia (Hasanuddin University, 2022)
Vibrio species in abattoir and aquaculture environment are of human health significance and may be increasing in pathogenicity and abundance. This study was aimed at determining the multidrug resistance of Vibrio species isolated from abattoir and aquaculture environment in Ebonyi state. Effluent samples were obtained from different abattoir sites within Ebonyi State from the butchers’ table, drainage, and wash water, while aquaculture sample were collected from different pond sites within the study area. Vibrio isolates were detected using Thiosulphate Citrate Bile Salt (TCBS) agar and identified based on the morphology and biochemical characterization. The results revealed a total of 50 isolates from 20 waste water samples. Waste water samples from different points of drainage water from abattoir had the highest microbial load of 3.85±0.35x106 CFU/mL. While, samples from butcher’s table and wash water from abattoir had high microbial load of 3.30±0.14x106and 3.25±0.14 x106 CFU/mL. respectively when compared to aquaculture samples which had the least microbial load of 0.6±3.9 x106 CFU/mL. Percentage antibiotic susceptibility profile showed Vibrio isolates were highly resistant to Tobramycin 40(80%), Cefoxitin 40(80%), amoxicillin/clavulanic acid 40(80%), Meropenem 30(52%), Cefepime28(56). Abattoir effluents and aquaculture are important reservoirs of multidrug resistant Vibrio pathogens. This implies that abattoir effluents could be important contributors to the episodes of epidemic cholera, non-Vibrio cholera and Vibrio causing illnesses in the study area.